Indicator of Nominalization Indicator as an Element of the Stylistic Characterization of Polish Book Reportages from 2004 to 2019 - Ostrowska, Katarzyna; Ruszkowski, Marek (Respectus Philologicus, 2024)
The most characteristic feature of each text regarding the frequency of parts of speech is the participation of nouns and verbs in it. The quantitative relationship between these two classes of words determines the level of nominalization, which can be calculated using the nominalization indicator (Wn). Its value is obtained from the sum of nouns divided by the sum of verbs in the text. The more verbs in relation to nouns, the more dynamic, spontaneous, and far from the orderly written Polish language the text is. The analysis of in contemporary Polish book reportages was conducted against a comparative background of 27 text types – spoken and written. Some of the reportages represent nominal styles (Wn > 3.0) and others present verbal styles (Wn < 1.5). Most texts, however, should be categorized as intermediate styles (1.5 ≤ Wn ≤ 3.0). This group includes the vast majority of the existing contemporary book reportages (the average value of Wn = 1.8), stretched between the life and dynamics of the description of facts and the intellectualization of their interpretation, which manifests itself in nominalization.
Keywords: parts of speech; nominalization indicator; book reportage